Towers and tanks for water-works the theory and practice of their design and construction - Hazlehurst, J. N. (John Wiley ; Chapman & Hall, 1904)
The inability to find any information on the increasingly popular water-tower resulted in the author, in 1901, plugging this apparent gap himself. His first edition was so successful that he quickly produced this second edition which also includes a record of stand-pipe failures and a chapter on stresses in steel water-towers.